DETERMINASI PERILAKU ORGANISASI TERHADAP KUALITAS SUMBER DAYA MANUSIA - Lastri Anggi Fani; Imalinda Deryane (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
This study aims to analyze the relationship between organizational behavior and the quality of Human Resources (HR). The results of this literature study highlight that organizational behavior can positively contribute to and improve the quality of human resources. Organizations with high quality human resources tend to be more effective and competitive. This study uses the literature study method to collect secondary data and analyze relevant theories. The results of this study provide a comprehensive view of how organizational behavior impacts HR quality and illustrates the importance of developing an organizational culture that supports employee growth and participation. The implication is that leaders and managers must focus on creating a positive work environment to foster human resource development and achievement of long-term goals